The Routledge companion to the geography of international business - Cook, Gary, 1961-; Johns, Jennifer (Economic geographer); McDonald, Frank, 1951-; Beaverstock, Jonathan V.; Pandit, Naresh R. (Routledge companions in business, management and accounting., 2018)
The fields of Economic Geography and International Business share an interest in the same phenomena, whilst each provides both a differing perspective and different research methods in attempting to understand those phenomena. The Routledge Companion to the Geography of International Business explores the nature and scope of inter-disciplinary work between Economic Geography and International Business in explaining the central issues in the international economy. Contributions written by leading specialists in each field (including some chapters written by inter-disciplinary teams) focus on the nature of multinational firms and their strategies, where they choose to locate their activities, how they create and manage international networks and the key relationships between multinationals and the places where they place their operations. Topics covered include the internationalisation of service industries, the influence of location on the competitiveness of firms and the economic dynamism of regions and where economic activity takes place and how knowledge, goods and services flow between locations. The book examines the areas for fruitful inter-disciplinary work between International Business and Economic Geography and sets out a road map for future joint research, and is an essential resource for students and practitioners of International Business and Economic Development.